INOVASI BOARD GAME MONOPOLI BERTEMA IKLIM SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF PADA SISWA SD DI PKBM EDUHOUSE - Noor Afida Rianda Putri; Sony Zulfikasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop and evaluate the feasibility of a climate-themed monopoly board game learning media called MISIK (Misi Iklim Kita) as an interactive learning medium for elementary school students at PKBM EduHouse Semarang. This research employed the 4D development model consisting of the define, design, develop, and disseminate stages. The research subjects included media experts, material experts, and users represented by teachers. Data collection techniques were conducted through observation, interviews, questionnaires, and documentation. The research instrument used a Likert scale to assess the feasibility aspects of the media. The results of the study showed that the development process through the 4D stages, namely Define, Design, Develop, and Disseminate, produced a learning media with a very high level of feasibility. The media expert validation obtained a percentage score of 96.2%, while the material expert validation reached 88.3%. In addition, user responses showed percentage scores of 91.6% and 86.6% with an average of 89.1%, all of which were categorized as highly feasible. These findings indicate that the MISIK monopoly board game meets the feasibility criteria for use in learning activities.